2020
DOI: 10.1002/app.49387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TPU hard segment content on the rheological and mechanical properties of PLA/TPU blends

Abstract: Blends of an amorphous polylactide (PLA) with three different thermoplastic polyurethane (TPU) grades having various hard segment (HS) contents are prepared at the blending ratio of 85/15 wt% through a twin‐screw extruder (TSE) at processing temperatures of 150 and 190°C. Blends of a semicrystalline PLA with 15 wt% of the noted TPU grades are also processed in the TSE at 190°C to investigate the matrix crystallization effect on the morphology and property enhancements. The rheological experiments reveal that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 49 publications
4
39
0
Order By: Relevance
“…The processing type and parameters also influence the blends morphology due to the changes in the applied shear and elongational forces as well as the changes in the viscoelastic properties and the viscosity ratios 42–44 . Therefore, besides processing at 250°C in TSE, the rPE/rPET system was also melt processed in TSE at 275°C where the PET phase could also completely melt and flow better.…”
Section: Resultsmentioning
confidence: 99%
“…The processing type and parameters also influence the blends morphology due to the changes in the applied shear and elongational forces as well as the changes in the viscoelastic properties and the viscosity ratios 42–44 . Therefore, besides processing at 250°C in TSE, the rPE/rPET system was also melt processed in TSE at 275°C where the PET phase could also completely melt and flow better.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have investigated the morphological and mechanical properties of PLA/TPU blends with and without using a compatibilizer 43–61 . Although some studies have reported that PLA and TPU are not compatible, 43–45 a few studies have shown that the ductility and impact strength of the PLA/TPU blends could be improved to some extent without the use of a compatibilizer while the strength and modulus were also decreased 44–49 .…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic polyurethane (TPU) is an elastomeric polymer with a unique combination of properties, such as high ductility, toughness, durability, flexibility, biocompatibility and biostability [51]. The molecular structure of TPU includes hard segments and soft segments.…”
Section: Introductionmentioning
confidence: 99%
“…TPU obtains rigidity and hardness from the crystalline domain of the hard segment, while the amorphous soft segment provides its flexibility and elastic behavior [52][53][54]. Several studies explored how the tensile strength and elastic modulus of the blends made by TPU-toughened PLA gradually decreased with the increase of TPU content, while the elongation at break and impact strength were greatly increased [47,50,51,[55][56][57][58][59]. Han et al [58] prepared PLA/TPU blends by melt blending, and the mechanical test results showed that the elongation at break of the blend increased greatly, while the yield strength decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation